Polarization imaging with enhanced spatial resolution - Peinado, A. (2015)
We present the design and the experimental implementation of a new imaging set-up, based on Liquid Crystal technology, able to obtain super-resolved polarimetric images of polarimetric samples when the resolution is detector limited. The proposed set-up is a combination of two modules. One of them is an imaging Stokes polarimeter, based on Ferroelectric Liquid Crystal cells, which is used to analyze the polarization spatial distribution of an incident beam. The other module is used to obtain high resolved intensity images of the sample in an optical system whose resolution is mainly limited by the CCD pixel geometry. It contains a calibrated Parallel Aligned Liquid Crystal on Silicon display employed to introduce controlled linear phases. As a result, a set of different low resolved intensity images with sub-pixel displacements are captured by the CCD. By properly combining these images and after applying a deconvolution process, a super-resolved intensity image of the object is obtained. Finally, the combination of the two different optical modules permits to employ super-resolved images during the polarimetric data reduction calculation, leading to a final polarization image with enhanced spatial resolution. The proposed optical set-up performance is implemented and experimentally validated by providing super-resolved images of an amplitude resolution test and a birefringent resolution test. A significant improvement in the spatial resolution (by a factor of 1.4) of the obtained polarimetric images, in comparison with the images obtained with the regular imaging system, is clearly observed when applying our proposed technique.